Haematological Indices and Antioxidant Enzyme Activity in Ghanaian Stroke Patients. (3rd March 2022) - Asmah, Richard Harry; Sackey, Pomah; Adjei, Patrick; Archampong, Timothy N.; Attoh, Seth; Doku, Derek; Quarchie, Marjorie; Botchway, Felix; Adedia, David; Donkor, Eric Sampene
Abstract : Background. Stroke is a cardiovascular disorder causing mortality globally and long-lasting harm worldwide. The disease occurs when the blood flow to the brain is either interrupted or blocked. This disruption leads to the increase in reactive oxygen species (ROS), especially superoxide free radicals, resulting in oxidative stress. The superoxide radicals are removed by superoxide dismutase (SOD), a key antioxidant enzyme. In this work, we investigated haematological indices and superoxide dismutase enzyme activity in Ghanaian patients with stroke and healthy control participants. Materials and Methods . Thirty stroke patients attending a stroke clinic and thirty apparently healthy control participants were recruited into the study. Blood samples were collected to determine haematological indices and SOD enzyme activity in red blood cells. Results. The stroke patients had significantly high blood parameters such as white blood cell (p < 0.001 ), neutrophil (p < 0.001 ), lymphocyte (p = 0.003 ), and eosinophil (p < 0.001 ) comparing with study participants without stroke, who were the control group in the study. Other blood parameters such as red blood cell, (p < 0.001 ), haemoglobin (p < 0.001 ), and haematocrit (p < 0.001 ) levels and mean cell haemoglobin concentration (p = 0.030 ), platelet (p = 0.010 ), and plateletcrit (p = 0.027 ) were high in stroke patients comparing with study control participants and statistically significant. Blood lymphocyte levels observed in stroke patients correlated negatively and significantly with SOD activity levels. SOD activity levels were significantly lower in stroke patients compared with the control group (p < 0.001 ). Low values of the antioxidant enzyme SOD activity levels, lymphocytes, and high values of plateletcrit were significant predictors of stroke. Conclusion . Haematological parameters such as WBC, lymphocyte, platelet levels, and red cell indices were significantly different in the stroke patients being studied. There was negative correlation between lymphocyte significantly with SOD activity and high oxidative stress in stroke patients compared with the control group. Lymphocytes and plateletcrit levels were also good predictors of the occurrence of stroke.